Color dilution alopecia in a Yorkshire - Magalhães, Tomás Rodrigues; Pinto, Filipe Fontes (Brazilian Journal of Veterinary Pathology, 2022)
A 1-year-old female Yorkshire terrier was presented to the clinic for a second opinion regarding its poor hair coat condition. According to the owner, the dog has been showing that appearance since the moment it was adopted, at 8 months of age. The owner also mentioned that the dog’s father had a similar fur appearance. External deworming was regularly administered to this dog, and oral fluralaner (Bravecto™) was given at the time of its presentation. No other clinical signs were reported. A complete physical examination was performed, with emphasis on skin and fur assessment. The main findings were the presence of extensive areas of hypotrichosis and alopecia, affecting only dark-haired regions, mainly in the dorsal region, neck and on the outer surface of both pinnae (Figs. 1 and 2). The presence of seborrhea and small papules compatible with superficial folliculitis were also identified. No other abnormalities were detected during the remaining examination. The complete blood count and serum biochemistry, including total circulating thyroxine (tT4) were unremarkable. Deep skin scraping and dermatophyte culture were also performed, but both tests were negative for the presence of ectoparasites and fungi, respectively. Finally, the hair follicles from the lesion areas were pulled out and evaluated under a microscope using the trichogram technique (Fig. 3). Baths with an anti-seborrheic and anti-microbial shampoo were prescribed, but although seborrhea and folliculitis were quickly controlled with this topical treatment, the alopecic areas remained and no signs of hair regrowth was observed in the following dermatological reassessments.